Inspirasi Alkitab: Sebuah Tinjauan Pandangan Tentang Inspirasi Alkitab di Gereja Masehi Advent Hari Ketujuh, Sebuah Studi Sejarah dan Teologi - Doloksaribu, Yohanes Verdianto (INTELEKTIUM, 2025)
The Seventh-day Adventist (SDA) Church believes that the Bible is the inspired word of God. The purpose of this study is to review the views of the SDA regarding the inspiration of the Bible from before the SDA organization was founded until now. This paper argues that there are several views among the pioneers and leaders of the SDA regarding the inspiration of the Bible. First, before the organization of the SDA, some held the view that divine inspiration extended to every word of the Bible, while others had the view that the Bible is the perfect word of God. After the SDA was organized in 1863, views regarding inspiration varied. Some held the view that there are degrees of inspiration in the Bible, while others believed that the Holy Spirit dictated the writing of the Bible to the prophets. Others, however, believed that the Bible is the only infallible rule of faith and practice. However, after 1883, within the SDA, there was only one view regarding the inspiration of the Bible: the SDA did not believe in verbal inspiration, but thought inspiration. This paper is a historical approach using the documentary research method.